2015
DOI: 10.1080/15287394.2014.979272
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Ultrastructural Study of Rat Liver Influenced by Electromagnetic Radiation

Abstract: Mobile communication systems are undoubtedly an environmental source of electromagnetic radiation (EMR). There is an increasing concern regarding the interactions of EMR with the humans. The aim of this study was to examine the effects of EMR on Wistar rat liver. Mature rats were exposed to electromagnetic field of frequency 2.45 GHz and mean power density of 2.8 mW/cm2 for 3 h/d for 3 wk. Samples of the liver were obtained 3 h after the last irradiation and processed histologically for light and transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
5
9
1
1
Order By: Relevance
“…There was moderate hyperaemia dilatation of liver sinusoids, and small inflammatory foci in the centre of liver lobules but no changes in the structure of the They also reported that there was occasional hepatocyte necrosis. These changes are in firm consistency with present work 11 . E.M. Brunts Knodell scoring had showed that there was a considerable damage was produced in the liver tissue after the 4G mobile phone radiation 5,10,20 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There was moderate hyperaemia dilatation of liver sinusoids, and small inflammatory foci in the centre of liver lobules but no changes in the structure of the They also reported that there was occasional hepatocyte necrosis. These changes are in firm consistency with present work 11 . E.M. Brunts Knodell scoring had showed that there was a considerable damage was produced in the liver tissue after the 4G mobile phone radiation 5,10,20 .…”
Section: Discussionsupporting
confidence: 93%
“…Though there were studies in which evidence of carcinomatous changes and oxidative stress produced by the release of free radicals due to radiation was reported, no such changes were observed in the present study 11,12,19 .…”
Section: Discussioncontrasting
confidence: 82%
“…They reach the conclusion that EMF damages the rat liver. Similar to the results of this study in that study, negative results were observed in the EMF group compared to the control group (25).…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that exposure to EMR of a frequency of 2.45 GHz and mean power density of 2.8 mW/cm 2 caused no pronounced morphological changes in the liver structure of 5-week old rats irradiated in utero as examined under light microscopy. However, our previous experiments revealed moderate hyperaemia, dilatation of liver sinusoids, and small inflammatory foci in the centre of liver lobules of 3-week-old rats that had been exposed to EMR postpartum (2.45 GHz, 3 h daily for 3 weeks) (Holovská et al 2015). Similar morphological changes induced by EMR in the liver of experimental animals were also observed by other authors.…”
Section: Discussionsupporting
confidence: 87%